2010
DOI: 10.1161/strokeaha.110.580647
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Mortality and Complications of Electively Clipped or Coiled Unruptured Intracranial Aneurysm

Abstract: Elective coiling of unruptured intracranial aneurysms is associated with fewer deaths and perioperative complications compared with elective clipping. The trend of hospital use of the coiling procedures has increased during recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(128 citation statements)
references
References 26 publications
11
110
4
3
Order By: Relevance
“…38 From this database, morbidity rates ranging from 13.5% to 27.6% and mortality rates ranging from 0.7% to 3.5% have been reported. 2,3,4,5,6,15,18,19,22,28,41 The objective of this institutional review board-approved prospective study was to assess the feasibility and efficacy of the addition of direct neurological testing during both temporary and permanent clipping of UIAs.…”
mentioning
confidence: 99%
“…38 From this database, morbidity rates ranging from 13.5% to 27.6% and mortality rates ranging from 0.7% to 3.5% have been reported. 2,3,4,5,6,15,18,19,22,28,41 The objective of this institutional review board-approved prospective study was to assess the feasibility and efficacy of the addition of direct neurological testing during both temporary and permanent clipping of UIAs.…”
mentioning
confidence: 99%
“…This trend of decreased morbidity and mortality observed in patients with AcomA aneurysm over time is consistent with the finding that morbidity and mortality rates have increasingly been reduced across time among a sample of patients treated with endovascular coiling in the United States (Nationwide Inpatient Sample). 28,33,34 These studies showed that morbidity rates decreased from 7. Across this time period stratification, our meta-analysis also showed that the overall aneurysm retreatment rate doubled from 5-10% when comparing studies published before and after 2007; however, the trend toward an increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…44 Numerous studies have shown a lower periprocedural morbidity and mortality associated with endovascular treatment and lower rates of discharge to long-term care facilities. 44,45 Some authors have suggested that Ͼ90% of aneurysms can now be effectively treated by using endovascular techniques. 46 However, the durability of coil embolization remains frequently debated due to the increased risk of residual aneurysm components or neck remnants, interval rupture or rebleeding (Ͻ1%), and the additional risk of retreatment.…”
Section: Efficacy and Safetymentioning
confidence: 99%